El deber de idoneidad y su alcance normativo en la contratación inmobiliaria, una mirada garantista a los derechos de los consumidores - Durand Carrión, Julio Baltazar (2023)
In real estate contracting, a consumer relationship is established between the real estate supplier and the end consumer. This consumer relationship implies a series of duties for the supplier, such as the duty of information and the duty of suitability. This second duty will be the focus of this paper. Within this framework, the paper will address the following points. First, we will develop, under the lens of the duty of suitability, the problem of real estate reorganization and abusive clauses. As a second point, we will make a problematization of the ad corpus clauses as abusive clauses. Finally, we will review the liability of suppliers’ managers in the real estate field. Throughout the work, we will rely on resolutions of the Instituto Nacional de Defensa de la Competencia y de la Protección de la Propiedad Intelectual (hereinafter, INDECOPI).